2006
DOI: 10.1097/01.pcc.0000227755.96700.98
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia is a marker for poor outcome in the postoperative pediatric cardiac patient*

Abstract: Hyperglycemia in the postoperative period was associated with increased morbidity and mortality in postoperative pediatric cardiac patient. Strict glycemic control may improve outcomes in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 29 publications
7
101
3
2
Order By: Relevance
“…They reported a 2.5-fold increased risk of dying if the maximum glucose obtained within 24 hours of admission to the ICU was >150 mg/dL. More recently, Yates et al 25 reported that hyperglycemia in the postoperative period was associated with increased morbidity and mortality in postoperative pediatric cardiac patients. Other studies in children with traumatic brain or head injury have also shown an association between poor neurological outcome and elevated admission blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a 2.5-fold increased risk of dying if the maximum glucose obtained within 24 hours of admission to the ICU was >150 mg/dL. More recently, Yates et al 25 reported that hyperglycemia in the postoperative period was associated with increased morbidity and mortality in postoperative pediatric cardiac patients. Other studies in children with traumatic brain or head injury have also shown an association between poor neurological outcome and elevated admission blood glucose.…”
Section: Discussionmentioning
confidence: 99%
“…68,69 Cardiopulmonary bypass is thought to result in SH through a combination of inflammatory cytokine release, vasoactive infusion use, pancreatic β-cell dysfunction, hypothermia with insulin resistance, and steroid use. 68 While some studies have demonstrated the association of SH with poor outcomes in children undergoing cardiac surgery 14,29,30,69,70 , other studies have not shown any impact of SH on long-term neurodevelopmental outcomes following cardiac surgery involving CPB. [71][72][73] Similar to CPB, ECLS is also associated with development of SH in critically ill children.…”
Section: Cardiopulmonary Bypass/extracorporeal Life Support and Stresmentioning
confidence: 99%
“…1,29 This association of SH with mortality appears across different pediatric disease states, including septic shock, burns, traumatic brain injury, post cardiac surgery, and trauma. [10][11][12][13][14][15][16] Additionally, SH is associated with longer periods of ICU and hospital stay and more frequent nosocomial infections, including surgical site infections in critically ill children. [2][3][4][5][6]29,30 While all these studies demonstrate strong associations between SH and poor clinical outcomes, they do not necessarily demonstrate a cause and effect relationship, because SH tends to be more marked in patients with greater illness severity.…”
Section: Stress Hyperglycemia In Pediatric Critical Illnessmentioning
confidence: 99%
See 2 more Smart Citations